A benefit-cost analysis of the conversion of agricultural lands at the urban fringe (case study of San Jose del Monte City, Bulacan) - Gabon, Abigail Mary V. (2005)
Agricultural lands at the vicinity of Metro Manila are under great pressure from land developers for conversion to other uses. Records show that in the City of San Jose del Monte (SJDM), Bulacan, a total of 353.96 hectares of agricultural lands were approved for conversion to mostly residential uses between the period of 1988-2000. Almost always, the land uses that displace agricultural lands at the urban fringe are the low-density residential subdivisions and commercial strip developments, which principally characterize urban sprawl. Urban sprawl has been the reason behind a number of environmental problems, which include traffic congestion, air pollution, the rapid absorption of farmlands and forests and the inadequacy of infrastructure and social facility provisions. There has been a growing sense of urgency on the rapid conversion of agricultural lands in SJDM, for the following reasons:(1) The impact of new land uses to agricultural lands is largely irreversible; and (2)The Conversion of agricultural land may result in many environmental problems, such as water quality degradation and flooding due to increased runoff. This study is focused on helping the local government unit of SJDM have a better understanding of the economic benefits and costs in maintaining agricultural lands compared to other types of land uses. This will also involve a survey on the public's preferences for the protection of agricultural areas. Information these may then pave the way for a more rational and integrated use of land resources within the city.